Periodic Eye Examinations among Ophthalmologists: Attitudes, Performance, and Barriers for Compliance - Dotan, Gad; Skaat, Alon; Gershoni, Assaf; Gaton, Dan D. (Current eye research, 2022)
Preventive eye care is a preferred practice that includes recommended regular eye examinations, which is not always followed. This study examined attitudes of ophthalmologists toward routine eye examinations, analyzed compliance with their own eye examinations, and described reasons for non-compliance. This was a cross-sectional study involving an online survey, sent to all members of the Israeli Ophthalmological Society (IOS) asking their personal opinions concerning routine eye care, self-performance of these tests, and reasons for non-compliance. A total of 243 responses were received (59% males, mean age 52 years) representing 40% of IOS members. 98% of respondents think that adults should be routinely screened for eye diseases, most commonly annually (52%) or every two years (36%); however, only 55% of ophthalmologists reported having themselves a routine eye check in the past 3 years, which is significantly lower than their spouse (68%, P = 0.003). Recommendations for routine eye examinations were always higher than their actual performance regardless of the responding ophthalmologists' gender, age or country of birth. Furthermore, female gender was found to be a negative predictor of having these examinations. Pupil dilation was performed in 38% of ophthalmologists' testing, even though 80% of them think it is necessary for a complete examination. 'Lack of time' (35%) and 'forgetfulness' (31%) were the main reasons provided by ophthalmologists as an explanation for not having regular eye testing. Ophthalmologists typically recognize the importance of preventive eye care, recommending periodic eye examinations for their patients; however, self-performance of these evaluations by the ophthalmologists themselves is much lower.